2014
DOI: 10.1080/09593330.2013.878396
|View full text |Cite
|
Sign up to set email alerts
|

Generalized regression neural network-based approach for modelling hourly dissolved oxygen concentration in the Upper Klamath River, Oregon, USA

Abstract: In this study, a comparison between generalized regression neural network (GRNN) and multiple linear regression (MLR) models is given on the effectiveness of modelling dissolved oxygen (DO) concentration in a river. The two models are developed using hourly experimental data collected from the United States Geological Survey (USGS Station No: 421209121463000 [top]) station at the Klamath River at Railroad Bridge at Lake Ewauna. The input variables used for the two models are water, pH, temperature, electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Artificial neural networks (ANNs) are an information processing system which belongs to the category of nonlinear models (Haykin 1999). ANNs are inspired from the function of the human brain.…”
Section: Multilayer Perceptron Neural Network (Mlpnn)mentioning
confidence: 99%
“…Artificial neural networks (ANNs) are an information processing system which belongs to the category of nonlinear models (Haykin 1999). ANNs are inspired from the function of the human brain.…”
Section: Multilayer Perceptron Neural Network (Mlpnn)mentioning
confidence: 99%
“…Singh et al [25] used water quality parameters to predict DO and biochemical oxygen demand in a river in India. Other studies (e.g., [26,27]) have used regression methods to predict DO in rivers using water temperature as inputs. In general, these studies have demonstrated that data-driven models can provide a suitable format for predicting DO with lower complexity [13].…”
Section: Data-driven Models and Annmentioning
confidence: 99%
“…Other studies (e.g. Heddam, 2014;Ay and Kisi, 2011) have used regression to predict DO in rivers using water temperature or electrical conductivity, amongst others, as inputs. In general, these studies have demonstrated that there is a need and demand for less complex DO models, have led to an increase in the popularity of data-driven models (Antanasijević et al, 2014), and shown that the performance of these types of models is suitable.…”
Section: Fuzzy Numbers and Data-driven Modellingmentioning
confidence: 99%